Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.5334/labphon.110
|View full text |Cite
|
Sign up to set email alerts
|

The role of intonation and visual cues in the perception of sentence types: Evidence from European Portuguese varieties

Abstract: Cruz, M., et al 2017 The role of intonation and visual cues in the perception of sentence types: Evidence from European Portuguese varieties. In this paper, we explore the role of intonation and visual cues in the perception of statements and questions in two varieties of European Portuguese-the standard (SEP) and the insular variety of Azores, Ponta Delgada (PtD)-previously shown to convey sentence type contrasts by different uses of intonational means and/or facial gestures, namely eyebrow movements. Forty n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 20 publications
(19 reference statements)
5
19
2
Order By: Relevance
“…In this way, visual cues may signal the information status of sentence elements, for example, to distinguish broad from contrastive focus (e.g., see Lambrecht, 1994, for a discussion). Visual cues are also used for the identification of statements versus questions (Borràs-Comes & Prieto, 2011; Cruz, Swerts, & Frota, 2017; House, 2002; Nicholson et al, 2003; Srinivasan & Massaro, 2003). In other words, given the multimodal nature of speech production, listeners perceive linguistic functions through the combination of acoustic and visual cues, both at segmental and suprasegmental levels of speech (Gili Fivela, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, visual cues may signal the information status of sentence elements, for example, to distinguish broad from contrastive focus (e.g., see Lambrecht, 1994, for a discussion). Visual cues are also used for the identification of statements versus questions (Borràs-Comes & Prieto, 2011; Cruz, Swerts, & Frota, 2017; House, 2002; Nicholson et al, 2003; Srinivasan & Massaro, 2003). In other words, given the multimodal nature of speech production, listeners perceive linguistic functions through the combination of acoustic and visual cues, both at segmental and suprasegmental levels of speech (Gili Fivela, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As noted in Frota et al (2014), the acquisition of the ability to recognize the question/statement sentence types is an important skill that is required in interaction contexts and in communication. Studies on the perception of sentence types in adult speech have shown that yes-no questions are perceived as such in different languages (Gussenhoven and Chen, 2000;Face, 2011;D'Imperio and House, 1997), including Portuguese (Falé and Faria, 2005;Cruz and Frota, 2011;Cruz et al, 2017).…”
Section: Previous Studiesmentioning
confidence: 99%
“…Results from perception tests revealed that native speakers from SEP are not able to recognize the difference between e-ISSN 2176-9419 statements and yes-no questions from ALE and PtD. Interestingly, native speakers from these varieties are able to distinguish between the sentence types (Cruz and Frota, 2011;Cruz et al, 2017). The findings on the native perception of ALE and PtD suggest that other cues might be relevant, besides the phonological units that compose the nuclear contours, possibly including cues from the pre-nuclear stretch.…”
Section: Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations